Non-Thermal Ultrasonic Extraction of Polyphenolic Compounds from Red Wine Lees - Filip Dujmić; Karin Kovačević Ganić; Duska Ćurić; Sven Karlović; Tomislav Bosiljkov; Damir Ježek; Rajko Vidrih; Janez Hribar; Emil Zlatić; Tihomir Prusina; Sucheta Khubber; Francisco J. Barba; et al. (Foods, 2020)
This study presents the results of conventional aqueous (CE) and non-conventional ultrasound-assisted (UAE) extractions of polyphenolic compounds from lees extracts of red wine varieties (Merlot and Vranac). The effect of ultrasound extraction time (t, s), and amplitude (A,%) from a 400 W ultrasound processor with different ultrasonic probes diameters (Ds, mm) on the amount and profile of polyphenolic compounds in the obtained extracts was investigated and compared to CE. The optimal conditions resulting in maximum extraction of phenolic compounds were: Probe diameter of 22 mm, amplitude 90% and extraction time for Vranac wine lees 1500 s and for Merlot wine lees extraction time of 1361 s. UAE proved to be significantly more effective in enhancing the extraction capacity of trans-resveratrol glucoside (30.57% to 300%), trans-resveratrol (36.36% to 45.75%), quercetin (39.94% to 43.83%), kaempferol (65.13% to 72.73%), petunidin-3-glucoside (41.53% to 64.95%), malvidin-3-glucoside (47.63% to 89.17%), malvidin-3-(6-O-acetyl) glucoside (23.84% to 49.74%), and malvidin-3-(6-O-p-coumaroyl) glucoside (26.77% to 34.93%) as compared to CE. Ultrasound reduced the extraction time (2.5-fold) and showed an increase of antioxidant potential by 76.39% (DPPH) and 125.83% (FRAP) compared to CE.